Presentación - Zegarra López, Fernando Elías (2023)
The strategic planning of national security involves the harmonization of the processes regulated in the regulations of Legislative Decree No. 1129, Legislative Decree that regulates the National Defense System, which has had difficulties in its implementation process, reflecting what was said by Carl Von Klausewitz, it is necessary to contemplate that the strategic environment will always be affected by the “fog” and “friction” that human nature itself – many times – reveals; To which is added the advance of modernity that we must not fail to attend to. In this sense, the Magazine of Defense Science and Research has considered – in this issue – articles related to technology, social conflicts that affect governance and higher education.